Surface-stimulation technology for grasping and walking neuroprostheses. - Popovic, M.R (IEEE Engineering in medicine and biology magazine)
Deals with improving the quality of life in stroke/spinal cord injury subjects with rapid prototyping and portable FES systems. Portable grasping and walking neuroprostheses, developed by the Automatic Control Laboratory at the Swiss Federal Institute of Technology Zurich (ETHZ) and the Paraplegic Center at the University Hospital Balgrist (ParaCare) are discussed. Both neuroprostheses employ surface stimulation technology and are currently used by a number of subjects in daily living activities